Implementasi Agenda Proyek Penguatan Profil Pelajar Pancasila (P5) Pada Tema Kearifan Lokal Guna Mendemonstrasikan Keanekaragaman Makanan Khas Samarinda di SMP Negeri 48 Samarinda - Siti Fatimah; Asnar Asnar; Wingkolatin Wingkolatin; Moh. Bahzar; Suryaningsi Suryaningsi; Novita Majid (Concept: Journal of Social Humanities and Education, 2024)
The aim of this research is to describe the implementation of the Project Agenda for Strengthening the Profile of Pancasila Students (P5) on the Theme of Local Wisdom to Demonstrate Typical Samarinda Food at SMP Negeri 48 Samarinda, as well as to find out the challenges and efforts in the Implementation of the Project Agenda for Strengthening the Profile of Pancasila Students (P5) on the Theme Local Wisdom to Demonstrate Typical Samarinda Food at SMP Negeri 48 Samarinda. The type of research used is descriptive qualitative, using observation, interview and documentation techniques. Data analysis techniques are data collection, data reduction, data presentation and conclusions. The results of the research show that in the Implementation of the Project Agenda for Strengthening the Profile of Pancasila Students (P5) on the Theme of Local Wisdom to Demonstrate Typical Samarinda Food at SMP Negeri 48 Samarinda that teachers and students understand the P5 agenda on the theme of local wisdom, the relevance of the P5 agenda on the theme of local wisdom in order to demonstrate Samarinda's typical food is very relevant to be implemented at SMP Negeri 48 Samarinda, and the connection and integration of P5 with the curriculum and Pancasila values ​​are closely related. The involvement of students is also very important in implementing the P5 agenda, then the existence of a learning community among teachers will create good collaboration, especially in making P5 teaching modules in implementing the P5 agenda on the theme of local wisdom.